Current issues on Hibinfection in Belarus, Kazakhstan and Russia - A.A. Baranov ("Paediatrician" Publishers LLC, 2006)
H. influenzae type B (HIB), is an important cause of serious infections in children, the second frequent in pneumonia and meningitis in children under 5. Every year it leads to an estimated 250-300 thousands of HIB associated meningitis all over the world with 40-50 thousands of lethal outcomes among them. The morbidity for HIB ameningitis in belarus, Kazachstan and Russia is 5 to 100000 of children under 5 year, it is 2 to 5 times higher for other HIB associated infections with possible regional variable levels. All of the numbers given are approximate estimations because the statistic data is insufficient. Accurate measurement of HIB disease burden is strongly needed. Along with that, increasing resistance of HIB to antibiotics arise much concerns. The article provides expert recommendations on HIB vaccination and measures to be taken for elimination of HIB infection. Key words: HIB infection, children, morbidity, vaccination.